1997
DOI: 10.1074/jbc.272.34.21296
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Spectroscopic Analyses of Mutants of a Conserved Histidine in the Metallophosphatases Calcineurin and λ Protein Phosphatase

Abstract: Calcineurin belongs to a family of serine/threonine protein phosphatases that contain active site dinuclear metal cofactors. Bacteriophage protein phosphatase is also considered to be a member of this family based on sequence comparisons (Lohse, D. L., Denu, J. M., and Dixon, J. E. (1995) Structure 3, 987-990). Using EPR spectroscopy, we demonstrate that protein phosphatase accommodates a dinuclear metal center. Calcineurin and protein phosphatase likewise contain a conserved histidine that is not a metal liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 39 publications
5
93
0
Order By: Relevance
“…Klee and co-workers (6) suggest the existence of superoxide-sensitive ferrous iron, but on the basis of spectroscopic and kinetic studies on isolated bovine CaN it was later suggested by Rusnak and co-workers (14,15) that native CaN exists in a redoxinsensitive Fe 3ϩ -Zn 2ϩ form. A redox-sensitive Fe 3ϩ -Fe 2ϩ form of CaN resembling the well characterized binuclear center in bovine spleen purple acid phosphatase was artificially obtained by metal exchange (14,16). It was hypothesized that this form could also contribute to redox sensitivity of native CaN in tissue homogenates (9,17).…”
mentioning
confidence: 99%
“…Klee and co-workers (6) suggest the existence of superoxide-sensitive ferrous iron, but on the basis of spectroscopic and kinetic studies on isolated bovine CaN it was later suggested by Rusnak and co-workers (14,15) that native CaN exists in a redoxinsensitive Fe 3ϩ -Zn 2ϩ form. A redox-sensitive Fe 3ϩ -Fe 2ϩ form of CaN resembling the well characterized binuclear center in bovine spleen purple acid phosphatase was artificially obtained by metal exchange (14,16). It was hypothesized that this form could also contribute to redox sensitivity of native CaN in tissue homogenates (9,17).…”
mentioning
confidence: 99%
“…PAPs' main function is protein dephosphorylation, which is the main mechanism in cell signal transduction pathways [72][73]75 and hence important cellular processes in general. Thus, PAPs have many significant biological functions.…”
Section: Paps' Biological Functionsmentioning
confidence: 99%
“…This is in agreement with previous studies. [72][73] Figure 23: SDS-PAGE analysis of the fractions collected from the chromatography of allantoic fluid on a gel filtration, Sephacryl S200 column, stained using Bio-Safe Coomassie G-250. The fractions contain pure pPAP as shown by the single band for each fraction (in the box).…”
Section: Ppap Extraction and Purificationmentioning
confidence: 99%
See 2 more Smart Citations